Trajektori Diplomasi Transaksional Pertukaran Tahanan antara Amerika Serikat dan Rusia - Julang Aryowiloto; Fitri Rofiyarti (Cenderawasih University, 2023)
Since the Cold War era, the United States (US) and Russia have practiced the same pattern of diplomatic relations, namely the exchange of prisoners. The exchange started in 1962 and continued to the most recent one in 2022. To this end, this article examines the trajectory of the prisoner exchange between the US and Russia through a descriptive qualitative approach complemented by a transactional diplomacy perspective. A chronology of prisoner exchanges between the two countries is presented in this study, along with the costs involved and the benefits received by each nation. From various exchange events between the US and Russia, it was found that the relationship pattern is transactionalism, tends to be bilateral and even ignores the multilateralism framework. The two countries have taken similar roles as the initiators of prisoners’ exchange. In addition to the roles, the positions of the two countries also alternate with one another. If the US acts as the initiator, Russia will be in a “wait and see” position and vice versa. In the end, bargaining position becomes the determining variable for who is in the “wait and see” position and who acts as the initiator.KEYWORDSPrisoner Exchange; Russia; The United States; Transactional Diplomacy